The West an illustrated history for children - Duncan, Dayton (Boston Little, Brown, 1996)
A presentation, based on a PBS television documentary, of the story of the West, a magnificent but harsh landscape, and the people who have tried to claim it.
Includes bibliographical references (p. 130-133) and index.
Keywords: West (U.S.) -- History -- Juvenile literature; West (U.S.) -- History